Pekerja seks jalanan : potensi penularan penyakit seksual - Pona, La (Yogyakarta : Universitas Gadjah Mada, 1998)
Street Prostitution and their risk of sexually transmitte in Jayapura City, Indonesia
Bibliography p. 61-63
In Indonesian, with summary in English
Keywords: Prostitution -- Indonesia -- Jayapura; Women -- Indonesia -- Jayapura -- Social condition; Teenagers -- Indonesia -- Jayapura; Sexually transmitted diseases -- Indonesia -- Jayapura